Considerações sobre a divisão social do trabalho segundo Hegel - Costa, Paulo de Tarso (2019)
To what extent does work objectify the meaning of man's life? It is a variable applied in Philosophy, being Hegel, one of the main authors who reflect on the transforming process of the same social phenomenon, since the work activity is the man that modifies the same and the environment in which it is inserted. Starting from this problematization, this dissertation focuses on a critical session of thought of Hegel, from three moments of his work, a saber: The System of Ethical Life, a Real Philosophy and Phenomenology of the Spirit. In short, the designation of the concept of social work. Therefore, it is believed that the work is a contribution to the philosophical debate, in that the action of the man on a woman reveals a questioning about the meaning of the work in the process of autonomy and human freedom.